2013
DOI: 10.5051/jpis.2013.43.5.227
|View full text |Cite
|
Sign up to set email alerts
|

Salivary soluble receptor activator of nuclear factor kappa B ligand/osteoprotegerin ratio in periodontal disease and health

Abstract: PurposeThe receptor activator of nuclear factor kappa B (RANK)/RANK ligand (RANKL)/osteoprotegerin (OPG) system plays a significant role in osteoclastogenesis, activation of osteoclasts, and regulation of bone resorption. This study aimed to evaluate the use of the salivary soluble RANKL (sRANKL)/OPG ratio as a diagnostic marker for periodontitis in nonsmokers.MethodsTwenty-five patients with chronic periodontitis and 25 individuals with a healthy periodontium were enrolled in this study. Samples containing 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
2
6
1
1
Order By: Relevance
“…Salivary samples were chosen for evaluation, as saliva is considered a diagnostic material, (18) abundant and has a simple sampling technique, fast and non-invasive; also, has no need for specialized equipment for its sampling. (19,20) The present study showed no statistically of visfatin in the present study showed cut-off values of 18.3 and 191.0 ng/ml, respectively. At these cutoff values, the diagnostic accuracy of visfatin as a marker for detecting OSCC and BEOLP is 100.0%.…”
Section: Discussioncontrasting
confidence: 56%
“…Salivary samples were chosen for evaluation, as saliva is considered a diagnostic material, (18) abundant and has a simple sampling technique, fast and non-invasive; also, has no need for specialized equipment for its sampling. (19,20) The present study showed no statistically of visfatin in the present study showed cut-off values of 18.3 and 191.0 ng/ml, respectively. At these cutoff values, the diagnostic accuracy of visfatin as a marker for detecting OSCC and BEOLP is 100.0%.…”
Section: Discussioncontrasting
confidence: 56%
“…Periodontitis is one of the most frequent oral diseases. It is a very important health issue that affects the patients' quality of life [22]. Periodontitis is diagnosed by clinical and radiographic criteria, which are not sufficient in determining the activity of the disease and the patient's susceptibility to the disease progression.…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, Tabari et al [22] show results similar to the current study: a significant increase of RANKL and RANKL/OPG ratio and a nonsignificant increase of OPG, but the salivary values of these biomarkers they reported are very different: 266 ± 48 pg/ml RANKL in the chronic periodontitis group, 207 ± 83 pg/ml RANKL for the healthy subjects, 2, 1 ± 1.0 pg/ml OPG in the CP group, and 2, 20 ± 7, 78 pg/ml OPG in the H group. Similar values as those of our study were reported by Hassan et al in 2015 [30], OPG 64, 5 ± 20, 9 pg/ml for the CP patients, and by Al-Ghurabi and Mohssen [31], in the same year, with a mean value for RANKL of 56, 8 pg/ml in the CP group.…”
Section: Resultsmentioning
confidence: 99%
“…Such results may also account for variant levels of subclinical inflammation among healthy subjects. Regarding salivary OPG levels, Tabari et al [ 44 ] failed to demonstrate a significant difference between healthy and CP patients while Costa et al [ 45 ] showed that it was higher in CP and diabetic patients than in the control group suggesting that OPG concentration could increase under circumstances that require the inhibition of osteoclastogenesis. Moreover, Garlet et al [ 15 ] observed equal prevalence of OPG expression in periodontitis patients and control, even a more intense expression was detected in the diseased group.…”
Section: Discussionmentioning
confidence: 99%